Water vapor adsorption by nanostructured polyphase compositions based on the solid component of welding aerosol - Tetyana L Rakitskaya; Alla S Truba; Alim A Ennan; Ruslan M Dlubovskii; Vitaliya Y Volkova (Adsorption Science & Technology)
The samples of the solid component of welding aerosols (SCWAs) formed in the electric arc plasma in the process of steel welding by electrodes of Ukrainian manufacture (ANO-4, ANO-21, UONI 13/55, and TsL-11,) differed in their chemical composition. The samples were characterized by X-ray phase analysis, IR spectroscopy, and water vapor ad/desorption. The results obtained allow suggesting the influence of a phase composition on the structural-adsorption properties of SCWAs.